2016
DOI: 10.1515/geochr-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Ring Response to Snow Cover and Reconstruction of Century annual Maximum Snow Depth for Northern Tianshan Mountains, China

Abstract: Heavy snowfall and extreme snow depth cause serious losses of human life and property in the northern Tianshan Mountains almost every winter. Snow cover is an important indicator of climate change. In this study, we developed five tree-ring-width chronologies of Schrenk spruce (Picea schrenkiana Fisch. et Mey) from the northern Tianshan Mountains using standard dendrochronological methods. Correlation analyses indicated that radial growth of trees in the northern Tianshan Mountains is positively affected by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
(34 reference statements)
2
9
0
1
Order By: Relevance
“…et Mey) forests are located in southern Kazakhstan and the northern slope of the Tianshan Mountains. Studies have shown that the tree‐ring growth of Schrenk spruce growing in arid and semi‐arid mountainous environments is climate‐sensitive and is very suitable for the reconstruction of past climate change (Yuan et al , , ; Zhang et al , , , ; Gao et al , ; Chen et al , ; Solomina et al , , ; Qin et al , ). Dendroclimatology is an important method for examining pre‐instrumental climate variations.…”
Section: Introductionmentioning
confidence: 99%
“…et Mey) forests are located in southern Kazakhstan and the northern slope of the Tianshan Mountains. Studies have shown that the tree‐ring growth of Schrenk spruce growing in arid and semi‐arid mountainous environments is climate‐sensitive and is very suitable for the reconstruction of past climate change (Yuan et al , , ; Zhang et al , , , ; Gao et al , ; Chen et al , ; Solomina et al , , ; Qin et al , ). Dendroclimatology is an important method for examining pre‐instrumental climate variations.…”
Section: Introductionmentioning
confidence: 99%
“…Various growth ring responses to snow cover indicate that the complex signals of the winter climate affect radial growth. Moreover, the positive and negative effects of snow cover may cancel each other out, leading to a relative equilibrium (Qin et al 2016;. In our study, it is also possible that snow cover measurements at the Kuujjuarapik climatic station (12 m a.s.l.)…”
Section: Yearmentioning
confidence: 83%
“…等方面有 着突出的贡献。树木的生长受到环境因素的限制作 用, 其长期的轮宽变化与气候、环境变化之间存在 一定的相关关系 Yin et al, 2016), 从 而使得树木的径向生长对气候、环境等因素具有较 为明确的响应 Qin et al, 2016;Wang et al, 2017)。 明确这种响应关系有助于评估气 候变化、环境变迁对树木生长的影响 (Rohner et al, 2016;Gao et al, 2017) (Xiao et al, 2016)。 由于柽柳独特的生长环境, 其埋藏亚化石样本可以应用于古环境的探究 (Lipp et al, 1996;Yang et al, 1996;Frumkin, 2009 BD, 班多村样本; RG, 然果村样本。P, 圆盘; X, 样芯。样本编号中的数字表示不同植株, 数字后字母表示多株合生树之分株。1), 显示髓心的树轮样本 年龄; 2), 未显示髓心的树轮样本最内轮年龄; 3), 该树芯样本包含不同株的两段, 其中内段样本未显示髓心。 DBH, diameter at breast height. BD, the specimen from Banduo Village; RG, the specimen from Ranguo Village.…”
Section: )以及树木生长对环境响应的评估(Babstunclassified